Nitrite stress increases staphylococcal enterotoxin C transcription and triggers the SigB regulon. Issue 1 (26th July 2022) - Etter, Danai; Büchel, Ramona; Patt, Tabea; Biggel, Michael; Tasara, Taurai; Cernela, Nicole; Stevens, Marc J A; Johler, Sophia
Abstract: Staphylococcal food poisoning is a common food intoxication caused by staphylococcal enterotoxins. While growth of Staphylococcus aureus is not inhibited by the meat-curing agent nitrite, we hypothesize that nitrite has an influence on enterotoxin C (SEC) expression. We investigated the influence of 150 mg/l nitrite on SEC expression at mRNA and protein level in seven strains expressing different SEC variants. Additionally, regulatory knockout mutants ( Δagr, ΔsarA, and ΔsigB ) of high SEC producing strain SAI48 were investigated at mRNA level. Our findings suggest that nitrite effectively increases sec mRNA transcription, but the effects on SEC protein expression are less pronounced. While Δagr mutants exhibited lower sec mRNA transcription levels than wildtype strains, this response was not stress specific. ΔsigB mutants displayed a nitrite stress-specific response. Whole genome sequencing of the strains revealed a defective agr element in one strain (SAI3). In this strain, sec transcription and SEC protein synthesis was not affected by the mutation. Consequently, additional regulatory networks must be at play in SEC expression. Comparison of our findings about SEC with previous experiments on SEB and SED suggest that each SE can respond differently, and that the same stressor can trigger opposing responses in strains that express multiple toxins. Abstract : Nitrite stress increases staphylococcal enterotoxin C transcription.